IL-21 Induces an Imbalance of Th17/Treg Cells in Moderate-to-Severe Plaque Psoriasis Patients - Shi, Yuling; Chen, Zeyu; Zhao, Zihan; Yu, Yingyuan; Fan, Huayu; Xu, Xiaoguang; Bu, Xiaolin; Gu, Jun (Frontiers in Immunology, 2019)
Background: Psoriasis is a chronic immune-mediated inflammatory skin disease, with over-activated interleukin (IL)-17-producing CD4+ T cells (Th17) and repressed regulatory T (Treg) cells. IL-21 is a Th17-related cytokine and plays an important role in the pathogenesis of psoriasis. However, the mechanism by which IL-21 affects the pathogenic progress of psoriasis remains poorly understood. Methods: IL-21 and IL-21 receptor (IL-21R) expression in normal and psoriatic lesional skin were determined by immumohistochemical staining, immunofluorescence staining, and western blotting. The levels of IL-21, IL-17A, and IL-22 in the culture supernatants were measured by enzyme-linked immunosorbent assay (ELISA). The level of IL-10 in the culture supernatants was measured by cytometric bead array (CBA). The mRNA expression levels were assessed by quantitative polymerase chain reaction (qPCR). CD4+ T cells were isolated from the peripheral blood mononuclear cells (PBMCs) from the psoriasis patients and healthy individuals and then treated with or without IL-21 for 3 days. The proportions of Th17 and Treg cells were determined by flow cytometric analysis. Results: IL-21 and IL-21R were highly expressed in the lesional skin and peripheral blood of psoriasis patients. IL-21 promoted CD4+ T cells proliferation and Th17 cells differentiation and inhibiting Treg cells differentiation by upregulating RORγt expression and downregulating Foxp3 expression, with increased expression and secretion of IL-17A and IL-22. The proportion of Treg cells was negatively correlated with that of Th17 cells in psoriasis patients. Conclusion: Our results suggest that IL-21 may promote psoriatic inflammation by inducing imbalance in Th17 and Treg cell populations.